2012
DOI: 10.1515/secm-2012-0049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polypropylene fiber on fracture properties of high-performance concrete composites

Abstract: A parametric experimental study has been conducted to investigate the effect of polypropylene fiber on the workability and fracture properties of highperformance concrete (HPC) composites containing fly ash and silica fume, with the five fiber volume fractions (0.04 % , 0.06 % , 0.08 % , 0.1 % , and 0.12 % ) used. The results indicate that the addition of polypropylene fiber decreases the workability of the HPC composites containing fly ash and silica fume. With the increase in the fiber volume fraction, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In recent years, increased work on the recycling of waste materials (Çimen, Saltan, & Keskin, 2015;Erdogmus, 2014) (Centonze, Leone, & Aiello, 2012;Gabor, Agnes, & Sandor, 2018;Gesoğlu, Güneyisi, Khoshnaw, & İpek, 2014;Mohsen, Saeed, Abolfazl, & Mana, 2017;Son, Hajirasouliha, & Pilakoutas, 2011;Thomas & Gupta, 2016) has accelerated the process. From these waste materials, in particular, the contribution of the steel fibers, on which researchers have been working on over the last 20 years, to concrete has revealed that it significantly improves mechanical properties and impact strength of concrete (Afroughsabet, Biolzi, & Monteiro, 2018;Babayev, Gürbüz, & Anadut, 2017;Djelloul, Menadi, Wardeh, & Kenai, 2018;Kim, Kim, Ha, & Kim, 2007;Koksal, Gencel, Unal, & Durgun, 2012;Koksal, Sahin, Beycioglu, Gencel, & Brostow, 2012;Köksal, Yiğit, Yerlikaya, & Şahin, 2005;Koroglu & Ozdoner, 2016;Sengul, 2016;Wang, Wu., & Li, 2000;Yavuz, Güler, Korkut, & Türkmenoğlu, 2016;Zhang & Li, 2012). In the last decade, steel wires from waste tires obtained from economical, innovative, environment-friendly industrial recyclable waste tires have been the interest of researchers (Bdour & Al-Khalayleh, 2010;Bjegovic, Bariceviv, & Lakusic, 2012;Domski, Katzer, Zakrzewski, & Ponikiewski, 2017;Koroglu, 2016Koroglu, , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, increased work on the recycling of waste materials (Çimen, Saltan, & Keskin, 2015;Erdogmus, 2014) (Centonze, Leone, & Aiello, 2012;Gabor, Agnes, & Sandor, 2018;Gesoğlu, Güneyisi, Khoshnaw, & İpek, 2014;Mohsen, Saeed, Abolfazl, & Mana, 2017;Son, Hajirasouliha, & Pilakoutas, 2011;Thomas & Gupta, 2016) has accelerated the process. From these waste materials, in particular, the contribution of the steel fibers, on which researchers have been working on over the last 20 years, to concrete has revealed that it significantly improves mechanical properties and impact strength of concrete (Afroughsabet, Biolzi, & Monteiro, 2018;Babayev, Gürbüz, & Anadut, 2017;Djelloul, Menadi, Wardeh, & Kenai, 2018;Kim, Kim, Ha, & Kim, 2007;Koksal, Gencel, Unal, & Durgun, 2012;Koksal, Sahin, Beycioglu, Gencel, & Brostow, 2012;Köksal, Yiğit, Yerlikaya, & Şahin, 2005;Koroglu & Ozdoner, 2016;Sengul, 2016;Wang, Wu., & Li, 2000;Yavuz, Güler, Korkut, & Türkmenoğlu, 2016;Zhang & Li, 2012). In the last decade, steel wires from waste tires obtained from economical, innovative, environment-friendly industrial recyclable waste tires have been the interest of researchers (Bdour & Al-Khalayleh, 2010;Bjegovic, Bariceviv, & Lakusic, 2012;Domski, Katzer, Zakrzewski, & Ponikiewski, 2017;Koroglu, 2016Koroglu, , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber Reinforced Concrete (FRC) behaves mechanically different from conventional concrete (Köroglu & Özdöner, 2016). FRC generally includes steel fiber , natural fibers (Bharath & Basavarajappa, 2016;Wei & Meyer, 2015), synthetic fibers (Amin, Foster, Gilbert, & Kaufmann, 2017;Macanovskis, Krasnikovs, Kononova, & Lukasenoks, 2017;Richardson & Ovington, 2017;Zhang & Li, 2012) and glass fibers (Tassew & Lubell, 2014). A Great number of experimental studies have been conducted (Köksal, Gencel, Unal, & Durgun Muhammed, 2012;Lee, Yi, & Oh, 2008;Li, Li, Shi, & Zhou, 2017;Liu, Lu, Wang, & Liang, 2017;Macanovskis et al, 2017;C.…”
Section: Introductionmentioning
confidence: 99%
“…A Great number of experimental studies have been conducted (Köksal, Gencel, Unal, & Durgun Muhammed, 2012;Lee, Yi, & Oh, 2008;Li, Li, Shi, & Zhou, 2017;Liu, Lu, Wang, & Liang, 2017;Macanovskis et al, 2017;C. S. Poon, Shui, & Lam, 2004;Tassew & Lubell, 2014;Varona, Baeza, Bru, & Ivorra, 2018;Zhang & Li, 2012) on the FRC including many parameters over the decades. However, using recycled materials in FRC have also been popular including steel wires extracted from waste tires.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, most research paid attention on the improvement effect of different types of fiber or optimum fiber content, but little literature paid attention on the difference of improvement effect by various stirring technologies. As a kind of new stirring technology, compared to traditional stirring technology, vibratory mixing technology could effectively improve the distribution of fibers in concrete, further increase the density of steel fiber concrete, and finally improve the mechanical properties of steel fiber-reinforced concrete [16][17][18][19][20]. But, at present, vibratory mixing technology has not been widely used in engineering, and research on its improvement of concrete mechanical properties is inadequate at home and abroad.…”
Section: Introductionmentioning
confidence: 99%